A Malaria Parasite Cross Reveals Genetic Determinants of Plasmodium falciparum Growth in Different Culture Media - Kumar, Sudhir; Li, Xue; McDew-White, Marina; Reyes, Ann; Delgado, Elizabeth; Sayeed, Abeer; Haile, Meseret T.; Abatiyow, Biley A.; Kennedy, Spencer Y.; Camargo, Nelly; Checkley, Lisa A.; Brenneman, Katelyn V.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
What genes determine in vitro growth and nutrient utilization in asexual blood-stage malaria parasites? Competition experiments between NF54, clone 3D7, a lab-adapted African parasite, and a recently isolated Asian parasite (NHP4026) reveal contrasting outcomes in different media: 3D7 outcompetes NHP4026 in media containing human serum, while NHP4026 outcompetes 3D7 in media containing AlbuMAX, a commercial lipid-rich bovine serum formulation. To determine the basis for this polymorphism, we conducted parasite genetic crosses using humanized mice and compared genome-wide allele frequency changes in three independent progeny populations cultured in media containing human serum or AlbuMAX. This bulk segregant analysis detected three quantitative trait loci (QTL) regions [on chromosome (chr) 2 containing aspartate transaminase AST; chr 13 containing EBA-140; and chr 14 containing cysteine protease ATG4] linked with differential growth in serum or AlbuMAX in each of the three independent progeny pools. Selection driving differential growth was strong (s = 0.10 – 0.23 per 48-hour lifecycle). We conducted validation experiments for the strongest QTL on chr 13: competition experiments between ΔEBA-140 and 3D7 wildtype parasites showed fitness reversals in the two medium types as seen in the parental parasites, validating this locus as the causative gene. These results (i) demonstrate the effectiveness of bulk segregant analysis for dissecting fitness traits in P. falciparum genetic crosses, and (ii) reveal intimate links between red blood cell invasion and nutrient composition of growth media. Use of parasite crosses combined with bulk segregant analysis will allow systematic dissection of key nutrient acquisition/metabolism and red blood cell invasion pathways in P. falciparum.